Democracy and rural development in Nigeria: Challenges and prospects - Yuguda, Madu Abdulrazak; Yusof, Rohana (2014)
Nigeria’s return to democratically elected government in 1999; after decades of Military rule and dictatorship since independence in 1960 has placed the country’s agenda on an agreed target by all and sundry, and this was accompanied by hopes, aspirations and expectations, due to the fact that, the countries development remains inadequate, most especially at the rural level which is regarded as most deprived and undeveloped.This paper therefore, attempts to examine the challenges and prospects of democracy on rural development in Nigeria from 1999-2014. The methodologies adopted in obtaining data for the paper are purely empirical and secondary.The paper contends that, democratic performance to bringing the desired changes and development in Nigeria remained abysmal and insignificant. It was concluded that for democracy to be meaningful; rural folk that accounted for the bulk of the country’s population must be developed otherwise the counties strides to been among one of the developednations will remain a mirage and unattained.